Silencing of crustacean hyperglycemic hormone gene expression reveals the characteristic energy and metabolic changes in the gills and epidermis of crayfish Procambarus clarkii - Li, Wen-Feng; Zhang, Shan; Chiu, Kuo-Hsun; Deng, Xiao-Yun; Yi, Yi (Frontiers in Physiology, 2024)
The crustacean hyperglycemic hormone (CHH) is a multifaceted neuropeptide instrumental in regulating carbohydrate and lipid metabolism, reproduction, osmoregulation, molting, and metamorphosis. Despite its significance, there is a dearth of research on its metabolic impact on the gills and epidermis-key organs in osmoregulation and molting processes. This study employed CHH dsRNA injections to silence CHH gene expression in Procambarus clarkii, followed by a metabolomic analysis of the gills and epidermis using nuclear magnetic resonance spectroscopy.Metabolic profiling through principal component analysis revealed the most pronounced changes at 24 hours post-injection (hpi) in the epidermis and at 48 hpi in the gills. At 24 hpi, the epidermis exhibited significant modulation in 25 enrichment sets and 20 KEGG pathways, while at 48 hpi, 5 metabolite sets and 6 KEGG pathways were prominently regulated. Notably, pathways associated with amino acid metabolism, carbohydrate metabolism, and cofactor and vitamin metabolism were affected. A marked decrease in glucose and other carbohydrates suggested a compromised carbohydrate supply, whereas increased levels of citrate cycle intermediates implied a potential boost in energy provision. The silencing of CHH gene expression hampered the carbohydrate supply, which was possibly the main energy derived substrates.Conversely, the gills displayed significant alterations in 15 metabolite sets and 16 KEGG pathways at 48 hpi, with no significant changes at 24 hpi. These changes encompassed amino acid, carbohydrate, and lipid metabolism pathways. The decline in TCA cycle intermediates pointed to a potential downregulation of the cycle, whereas a decrease in ketone bodies indicated a shift towards lipid metabolism for energy production. Additionally, increased levels of nicotinate, nicotinamide, and quinolinate were observed in both organs. Overall, CHH's impact on the epidermis was prominent at 24 hpi and diminished thereafter, whereas its influence on metabolism in gills was delayed but intensified at 48 hpi. This differential CHH effect between gills and epidermis in P. clarkii provides new insights into the organ-specific regulatory mechanisms of CHH on energy metabolism and osmoregulation, warranting further comparative studies to elucidate the distinct roles of CHH in these organs.